Design, synthesis, and biological evaluation of aminopyrazine derivatives as inhibitors of mitogen-activated protein kinase-activated protein kinase 2 (MK-2). Issue 22 (15th November 2015) - Lin, Songnian; Malkani, Sunita; Lombardo, Matthew; Yang, Lihu; Mills, Sander G.; Chapman, Kevin; Thompson, James E.; Zhang, Wen Xiao; Wang, Ruixiu; Cubbon, Rose M.; O'Neill, Edward A.; Hale, Jeffrey J.
Graphical abstract: Abstract: Several series of novel non-thiourea-containing aminopyrazine derivatives were designed based on the MK-2 inhibitors 1-(2-aminopyrazin-3-yl)methyl-2-thioureas. These compounds were synthesized and evaluated for their inhibitory activity against MK-2 enzyme in vitro. Compounds with low micromolar to sub-micromolar IC50 values were identified, and several compounds were also found to be active in suppressing the lipopolysaccharide (LPS)-stimulated TNFα production in THP-1 cells with minimum shift compared to their enzyme activity.